Dose comparison of two imaging techniques for the detection of myeloma lesions. (September 2016) - Tsionopoulou, P.; Kordolaimi, S.; Athanasakos, T.; Sideri, N.; Papakonstantinou, O.; Sakellaropoulos, G.; Nikiforidis, G.; Efstathopoulos, E.
Abstract : Introduction: Multiple myeloma (MM) is a hematological malignancy, theactivity of which is not clear yet. Skeletal survey and computed tomography are two commonly used imaging techniques for the detection of myeloma lesions. Purpose: The aim of this study is to compare the effective doses received by patients suspected for MM who were simultaneously evaluated with radiographs and whole body CT (WBCT) scan. Materials and methods: Patients underwent a conventional radiography (CR) and a computed tomography (CT). Concerning CR, seventeen views of human body were obtained for 10 patients and the effective dose (ED) was then estimatedutilizing the dose area product (DAP)-to-ED conversion coefficients reported in NRPB-R262 (whole body except for extremities) and NRPB-W4 (for extremities). Forthe CT examinations, the acquisition and dosimetric data of 53 patients undergone WBCT either withfiltered back-projection (FBP) or iterative reconstruction (iDose, Philips) algorithm were retrospectively recorded and ED was estimated by utilizing sex- and age- specific DLP-to-ED conversion factors available in literature. Results: The ED of the patients underwent WBCT were2.33 ± 1.14 mSv and 7.06 ± 6.16 mSv for iDoseand FBP protocols, respectively while the corresponding ED from the CR procedures were 2.12 ± 0.80 mSv. Conclusion: Low radiation exposure, almost equal to that of CR, can be achieved with the CT scan when iterative reconstruction algorithm is implemented in the acquisition data.